2007
DOI: 10.1080/14786430701394041
|View full text |Cite
|
Sign up to set email alerts
|

Investigating carbonization and graphitization using electron energy loss spectroscopy (EELS) in the transmission electron microscope (TEM)

Abstract: Electron energy loss spectroscopy (EELS) in the transmission electron microscope (TEM) is explored as a useful characterization technique in the study of carbonization and graphitization of organic precursors. A model series of carbon materials was prepared from highly graphitizable petroleum pitch heat treated in the range 200-2730 C. Initial characterization was performed using the established techniques of X-ray diffraction (XRD), He pycnometry, TEM, electron diffraction and high-resolution lattice imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 30 publications
8
105
0
Order By: Relevance
“…1 eV. This implied a slight reduction in density following neutron irradiation, possibly as a result of an increase in low density material at crystallite grain boundaries following crystallite fragmentation (as observed from XRD and Raman) and/or an increase in nanoporosity [37]. However, the data was also highly variable over different areas.…”
Section: Tem/eelsmentioning
confidence: 74%
“…1 eV. This implied a slight reduction in density following neutron irradiation, possibly as a result of an increase in low density material at crystallite grain boundaries following crystallite fragmentation (as observed from XRD and Raman) and/or an increase in nanoporosity [37]. However, the data was also highly variable over different areas.…”
Section: Tem/eelsmentioning
confidence: 74%
“…There are publications suggesting ways to process EELS data, claiming advantages and drawback of the methods [4,5,24]. Zhang et al [4] suggested a three Gaussian's peak fitting for the core loss; Daniels et al [24] suggested the data processing for low loss. Both methods are used in this study for the core loss and low loss spectra collected, respectively.…”
Section: D /I G Ratio Is (Zddp-wdlc) > ((Modtc+zddp)-wdlc) > (Gmo-wmentioning
confidence: 99%
“…Both EELS and Raman are historically used to characterize the carbon based materials [3,4,24,25]. The bulk material properties can be easily investigated by Raman in a qualitative way for a micrometre resolution [3].…”
Section: Eels Study On Friction and Coating Structurementioning
confidence: 99%
See 2 more Smart Citations